Merger and Acquisition: Do They Really Creates A Synergy Effect? - Gadis Arimbi Puspita; Irni Yunita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
As competition continues to intensify across various industry sectors, companies are compelled to formulate strategies to remain competitive. One commonly used strategy is expansion through Mergers and Acquisitions (M&A), which, in theory, should create synergy and added value for the company. This research aims to test the effects of post-merger synergy, specifically operational synergy tested using Sales Growth and Earnings Per Share (EPS), and financial synergy tested using Debt Equity Ratio (DER). The study examined 17 companies that underwent M&A during the years 2015-2019, with a testing period of 3 years before and after the events, divided into 12 quarters. The research results indicate no significant differences in the three variables. Meanwhile, the synergy level tests using Gain Score Analysis show that 58.82% of companies did not experience operational synergy, as tested using Sales Growth. Furthermore, 64.71% of companies did not experience operational synergy, as tested using Earnings Per Share (EPS). Additionally, 47.06% of companies did not experience financial synergy, as tested using Debt Equity Ratio (DER).